The Effectiveness of Using Lontara Bugis Makassar Script in English Vocabulary Teaching - Purnama, Atmaranie Dewi; Aminah, Sitti; Kareba, Andi Muammar; Harmilawati (JLE: Journal of Literate of English Education Study Program, 2024)
Vocabulary teaching, especially in early childhood, must be emphasized, because having sufficient vocabulary will make it easier for children to communicate. The Lontara script is a regional language that is now almost forgotten by the younger generation; therefore, this research tries to integrate the Lontara script in learning English vocabulary. The type of research used in this research is quantitative research with experimental methods. In this study, researchers used the One-Group Pre-Test-Post-Test Design. The data obtained can be interpreted to be in positive ranks, with an average value (mean ranks) equal to 24.50, and a total value (sum of ranks) equal to 1176.00. This means that there is an increase in post-test scores after treatment, which means that the integration of Lontara Bugis script in learning English vocabulary is effective in improving understanding of English vocabulary for fifth-grade students at MI Darul Abrar Balle Village, MIS Arrahman Labuaja, and MIS UKI Siputanre Cakkela, which are in Kahu District, Bone Regency, South Sulawesi Province.